Padrões físicos inadequados na performance da trompa - Sarah Ramez Ferreira (2009)
Playing musical instruments requires from instrumentalists a great physical effort. Due to repetitive effort, the instrumentalists. bodies may suffer physicals alterations, related to the practice and performance of the diverse instruments. Consequently, musicians may have muscular problems, as well as physical discomfort and pain. As any other instrumentalists, french horn players are vulnerable to these problems. However, not many studies deal with the physical problems presented by french horn players. The present study investigated the inadequate physical patterns that may emerge due to the performance of the french horn. A literature review was done, which included studies on Human Anatomy and Physiology and well as studies that deal with the physical problems of musicians in general and specifically in french horn players. The research.s empirical data was gathered by means of observation of the performance of eight professional french horn players. The films were sent to a panel of specialists a doctor, a physiotherapist, an Alexander Technique teacher and a french horn teacher. Additionally, data were obtained through questionnaires, filled in by the eight trompists, subjects of the research, in which they revealed their physical difficulties while playing the instrument. The observations done by the panel of specialists indicated the existence of some inadequate physical patterns in the eight french horn players, as follows: head protusion; neck retification; lateral rotation of the head for the left side; left shoulder elevation; protusion of the left shoulder; projection of the superior trunk; rotation of the superior trunk for the right side; lumbar lordosis; pelvic projection and excessive tension in some segments of the body. Due to the incidence of these problems, it was done a discussion on how french horn teachers can deal with these inadequate physical patterns, in order to avoid them in their pedagogy. Some recommendations were offered in this sense. It was concluded that, due the asymmetrical ergonomics of the french horn, the french horn players tend to present inadequate physical patterns inherent to their performance, which should be understood and prevented in the pedagogy of the french horn.